Differences in Interval Training and Fartlek Training Methods on Increasing VO2MAX in Pembalang FC Regency Football Players North Luwu - Ibrahim, Sultan Akbar; Raharjo, Bambang Budi; Raharjo, Agus (Journal of Physical Education and Sports, 2023)
This research aims to increase VO2max in Pembalang FC football players, and this is realized in the form of research using Interval Training (IT) Exercises and Fartlek Exercises to Increase VO2max for Pembalang FC Football Players. Through the theme raised by this research, it is hoped that it can be a solution for the Pembalang FC football team to overcome the problems of the players and the team itself. The research design that the author used in this research was a pre-experimental design. This research will use a total sampling technique by taking the entire population, namely 30 people. Then they will be divided into two training groups, each consisting of 15 people. This research will use a total sampling technique by taking the entire population, namely 30 people. Then they will be divided into two training groups, each consisting of 15 people. 2 on the Independent Sample t test on Interval training and Fartlek training. The basis for decision making to determine the difference is if the sig (2-tailed) value is < 0.05 then there is a significant difference, if the sig (2-tailed) value is > 0.05 then there is no difference. The results obtained in the difference test are sig. (2-tailed) > 0.05 so it can be concluded that there is no difference in the increase in VO2Max between Interval Training and Fartlek training.